The association between triglycerides/high-density lipoprotein cholesterol ratio, insulin resistance, and serum androgen levels in patients with polycystic ovary syndrome - Ulutaş, Firdevs; Cander, Soner; Öz Gül, Özen (The European Research Journal, 2022)
Objectives: Insulin resistance and dyslipidemia are common comorbidities of polycystic ovary syndrome. We aim to evaluate the association between triglycerides/high-density lipoprotein cholesterol ratio, insulin resistance, and serum androgen levels in patients with polycystic ovary syndrome. Methods: We enrolled a total of 40 polycystic ovary syndrome patients and 20 healthy control subjects in this cross-sectional study. The polycystic ovary syndrome patients were divided into two subgroups obese and non-obese. The triglycerides/high-density lipoprotein cholesterol ratio and homeostatic model assessment of insulin resistance were calculated for all individuals. Demographic characteristics, serum levels of metabolic parameters, and androgens were compared between the study subgroups. P-value < 0.05 was accepted as statistically significant. Results: The triglycerides/high-density lipoprotein cholesterol ratio was higher in obese polycystic ovary syndrome patients than in other groups (3.64 ± 3.06 vs. 1.07 ± 0.36 in control and 1.18 ± 0.53 in non-obese group, p < 0.005). The triglycerides/high-density lipoprotein cholesterol ratio was positively correlated with homeostatic model assessment of insulin resistance (r=0.546, p < 0.001), total testosterone (r=0.402, p = 0.010), and free androgen index (r=0.609, p < 0.001) while was negatively correlated with sex hormone-binding globulin (r=-0.497, p = 0.001). Obese polycystic ovary syndrome patients had higher serum total testosterone levels, higher free androgen index, and lower sex hormone-binding globulin than non-obese polycystic ovary syndrome patients (0.71 ± 0.49 ng/mL vs. 0.45 ± 0.16 ng/mL, p = 0.006; 3.1 ± 1.91 vs. 1.01 ± 0.49, p < 0.005; and 26 ± 10.3 nmol/L vs. 59.6 ± 43.7 nmol/L, p < 0.005, respectively). Obese polycystic ovary syndrome patients had also worse lipid parameters, including high triglycerides and low high-density cholesterol when compared with other groups. Conclusions: The triglycerides/high-density lipoprotein cholesterol ratio was correlated with the homeostatic model assessment of insulin resistance, and androgenic hormonal profiles including total testosterone and free androgen index in patients with polycystic ovary syndrome.